ANALISIS PENGARUH LEVERAGE, FINANCIAL PERFORMANCE FIRM SIZE DAN SALES GROWTH TERHADAP FIRM VALUE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Fenty Fauziah; Sri Wahyuni Jamal (RJABM (Research Journal of Accounting and Business Management), 2020)
This study aims to analyze the effect of leverage, financial performance, firm size and sales growth on firm value. The study population is all manufacturing companies listed on the Indonesian stock exchange, the period 2017 - 2018. The sample selection uses a purposive sampling method. Data analysis and hypothesis testing were carried out using a structural equation modeling approach using the Eviews 11. The results showed that financial performance and sales growth had a significant effect on firm value. investors in making investment decisions view the level of profitability from their ability to manage assets. The ability to manage assets creates sales growth so that it can get maximum profit. Both of these things can increase the company's value in the market. Investors in making investment decisions generally do not consider several factors as a whole, so that the right investment decisions will be obtained.